2014
DOI: 10.1007/s11356-014-3542-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertilization on the acidity and salinity of greenhouse soils

Abstract: A greenhouse pot experiment was conducted to study the effects of conventional nitrogen fertilization on soil acidity and salinity. Three N rates (urea; N0, 0 kg N ha(-1); N1, 600 kg N ha(-1); and N2, 1,200 kg N ha(-1)) were applied in five soils with different greenhouse cultivation years to evaluate soil acidification and salinization rate induced by nitrogen fertilizer in lettuce production. Both soil acidity and salinity increased significantly as N input increased after one season, with pH decrease rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
4
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 42 publications
4
83
4
5
Order By: Relevance
“…Soil pH, organic matter (OM) and 10 the various P accumulation characteristics were investigated. We found that soil pH in PGVS were 11 significantly decreased by 0.57~1.17 unit with obvious signs of acidification, compared with that in 12 OVS. Soil OM was different for different sampling locations, but in general it was higher in PGVS 13 than OVS.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Soil pH, organic matter (OM) and 10 the various P accumulation characteristics were investigated. We found that soil pH in PGVS were 11 significantly decreased by 0.57~1.17 unit with obvious signs of acidification, compared with that in 12 OVS. Soil OM was different for different sampling locations, but in general it was higher in PGVS 13 than OVS.…”
mentioning
confidence: 69%
“…By 11 comparison, the amount of T-P i in PGVS was significantly higher than that of OVS in S2, S3 and 12 S4 (Table 3).…”
mentioning
confidence: 88%
“…They are therefore suitable for crop production in the cold regions of northern China [1,2], and provide much higher yields and incomes than open field cultivation [3,4]. However, microclimate factors in greenhouses, such as the temperature, lightintensity, humidity, and aeration, and management methods, including tillage and fertilization, can give rise to soil acidification, secondary salinization, and nutrient enrichment and unbalance [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the previous experiments showed that fertilization with high amounts of N 2 increased globulin relative to other fractions of oat protein [28]. Consequently, an increase in protein content here may be due to the capacity for maximum absorption of nitrogen in the container-grown plants in the greenhouse due to less percolation compared with soil in the field, which allows maximum permeation or percolation [29]. This could probably increase the globulin fractions that eventually gave a high protein percentage.…”
Section: Discussionmentioning
confidence: 77%